Pseudogene-Derived lncRNAs and Their miRNA Sponging Mechanism in Human Cancer - Lou, Weiyang; Ding, Bisha; Fu, Peifen (Frontiers in Cell and Developmental Biology, 2020)
Pseudogenes, abundant in the human genome, are traditionally considered as non-functional “junk genes”. However, recent studies have revealed that pseudogenes act as key regulators at DNA, RNA or protein level in diverse human disorders (including cancer), among which pseudogene-derived long non-coding RNA (lncRNA) transcripts are extensively investigated and has been reported to be frequently dysregulated in various types of human cancer. Growing evidence demonstrates that pseudogene-derived lncRNAs play important roles in cancer initiation and progression by serving as competing endogenous RNAs (ceRNAs) through competitively binding to shared microRNAs (miRNAs), thus affecting both their cognate genes and unrelated genes. Herein, we retrospect those current findings about expression, functions and potential ceRNA mechanisms of pseudogene-derived lncRNAs in human cancer, which may provide us with some crucial clues in developing potential targets for cancer therapy in the future.